PENGGUNAAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA KELAS III SD NEGERI 1 SANGUBANYU - TIYANI, SULIS (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation of Realistic Mathematics Education (RME) Approach in Improving Mathematics Learning at The Third Grade Students of SDN 1 Sangubanyu in The Academic Year of 2013/2014. The objectives of this study are to describe the learning steps, the learning improvement, and problems and solutions in the implementation of RME approach in improving Mathematics learning about two-dimensional shape at the third grade students of SDN 1 Sangubanyu in the academic year of 2013/2014. This research is Class Action Research (CAR) implemented in three cycles. Each cycle consists of planning, action, observation, and reflection. The subjects were all students of third grade in SDN 1 Sangubanyu in the academic year of 2013/2014, amounting to 17 students. The results show that the implementation of Realistic Mathematics Education (RME) approach can improve Mathematics learning at the third grade students.